All male Tilapia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Scientists at the University of Wales, Swansea, UK have developed a way to produce all male Tilapia fish biologically. Until now, this could be achieved only by treating Tilapia fingerlings with hormones, which can present problems. All male...